Mapping the Landscape of Sharia Economics: A Bibliometric Analysis - Syamsu Rijal (Westscience Press, 2023)
This study aims to conduct a bibliometric analysis to map the general landscape of Islamic economics using data from relevant scientific literature. Bibliometric methods are used to identify, collect, and analyze publications related to Islamic economics. Data are obtained from major academic sources, such as scientific journals, conferences, and books indexed in related databases. After data collection, appropriate bibliometric analysis techniques are applied to analyze trends, patterns, and developments related to the Islamic economy. Relevant bibliometric parameters, such as number of publications, most prolific authors, institutional affiliations, countries, and most frequently cited journals, are used to identify important factors in the Islamic economy. The results of this analysis will provide a clear picture of the development of the Islamic economy, helping researchers, practitioners, and other stakeholders in understanding trends and contributions of related scientific literature. This research will provide valuable insights and a better understanding of how Islamic economic concepts have been researched and applied in a global context.